2014
DOI: 10.11604/pamj.2014.18.258.3054
|View full text |Cite
|
Sign up to set email alerts
|

L’évaluation d’un programme d’éducation thérapeutique chez le patient diabétique dans un Centre Hospitalier Universitaire marocain: résultats préliminaires d’une enquête pilote

Abstract: L’éducation thérapeutique est fondamentale. Elle n'a pas uniquement pour effet la préservation du capital de santé par le meilleur contrôle métabolique, favorisé par la responsabilisation et l'autonomie. En effet, en se soignant mieux, le diabétique peut améliorer sa qualité de vie, et en retirer un bénéfice qui va au-delà de la satisfaction de préserver son avenir. L'objectif principal de cette étude était de déterminer le nombre des patients diabétiques ayant bénéficié d'une éducation thérapeutique, la relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4). In Mali, diabetes treatment accounts for 70% of the patient's income, making it difficult to adhere to treatment [[16], [17], [18], [19], [20]], as well as in developing countries, where poverty is a major barrier to the management of chronic diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…4). In Mali, diabetes treatment accounts for 70% of the patient's income, making it difficult to adhere to treatment [[16], [17], [18], [19], [20]], as well as in developing countries, where poverty is a major barrier to the management of chronic diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate glycaemic control is recommended in both type 1 and type 2 diabetic patients to delay the onset of complications, 9 , 10 improve the quality of life of patients and at the same time reduce the high cost of diabetes care for the health sector. 7 , 8 , 10 However, as it is with other chronic diseases, very few diabetic patients consult on time to obtain optimal medical intervention and treatment for their diseases because of multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate glycaemic control is recommended in both type 1 and type 2 diabetic patients to delay the onset of complications, 9 , 10 improve the quality of life of patients and at the same time reduce the high cost of diabetes care for the health sector. 7 , 8 , 10 However, as it is with other chronic diseases, very few diabetic patients consult on time to obtain optimal medical intervention and treatment for their diseases because of multiple factors. 11 The prevalence of poor glycaemic control varies, from 29% to 73% in diabetic patients aged greater than or equal to 65 in the United States (US), 12 65% in France, 13 71% in East, West and Central Africa 14 and 68% in the DRC.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the eating behavior of people with diabetes showed that their regime includes a high percentage of lipids (mainly monounsaturated fatty acid) and proteins [ 54 ]; while fish consumption was low, they largely consumed cold meat, cheese, green vegetables (which are part of traditional Moroccan food, in particular tajine and couscous). Another study evaluating therapeutic education showed that the vast majority of Moroccan diabetics (91%) receive education about hygienic measurements, diet, and glycemic self-control (98.0%) [ 55 ]. The same study indicated that 34% of diabetes patients do not respect this education.…”
Section: Cvd Risk Factorsmentioning
confidence: 99%